O desafio do manejo das dificuldades alimentares na infância: uma análise crítica do guia de orientações da Sociedade Brasileira de Pediatria - Lígia Cardoso dos Reis; Viviane Laudelino Vieira; Daniela Neri (Universidade do Estado do Rio de Janeiro, 2023)
The Brazilian Society of Pediatrics (SBP) published In April 2022 some guidelines for managing feeding difficulties (FD) in collaboration with DANONE Nutricia®. This article critically analyzes the publication, highlighting its conceptual weaknesses. The following topics were identified: presence of conflict of interests, inaccuracies in the definition and prevalence of FD, lack of a clear definition for adequate and healthy eating, a nutrient-centered approach and lack of contextualization of FD with the food and nutritional panorama of Brazilian children. FD literature is scarce, with many publications declaring conflict of interests due to the authors' services provision to the food or pharmaceutical industry. Food preferences are determined by a complex interaction between intrinsic and extrinsic factors. Therefore, it is to be expected that a publication on infant feeding highlights the influence of social, environmental and current food system aspects on the eating patterns of children and families. Despite the evidence currently available, the publication of the SBP proposes a focus on the biological consequences of FD, on management with a restricted objective of ensuring adequate energy/nutritional intake, on monitoring the child's growth / development and on the discussion of solutions for FD that rely on food products that can be classified as ultra-processed. It can be concluded that the lack of a robust theoretical framework free of conflict of interests being used in the construction of the proposed recommendations prevents guidelines from supporting the qualification of comprehensive care for children's health.